Kaidah Pengulangan Lafaz dalam al-Qur’an: Studi Analisis QS. an-Naml[27]: 60-64 - Wulandari, Dewi; Yusuf, Moh.Asror; Marhumah, Qoidatul (Canonia Religia, 2023)
This article aims to examine the meaning of the repetition of phrases (tikrār) found in QS.  an-Naml [27]: 60-64. These verses briefly discuss faith in Allah as a very important teaching and a core aspect of human life. Therefore, it is interesting to explore the meaning of the repetition of phrases implied in the verses that discuss this creed. Some research questions to be answered are: first, what is the meaning of the repetition of phrases in QS. an-Naml [27]: 60-64?; second, what wisdom is contained in this repetition of phrases? The research method used in this study is descriptive-analytical method. Based on the research findings, it is concluded that the meaning of the repetition of phrases in QS. an-Naml [27]: 60-64 is a "confirmation" that is present in the phrase "amman" at the beginning of each verse and signifies a "denial" in the phrase "a‘ilāhun ma'a Allāh" in the middle of the verse, with each repeated five times. The repetition serves as an affirmation of the evidence of Allah's oneness in the face of so many creations in the world, all of which are under Allah's power without the interference of anyone else. The meaning of denial is to negate that anything deserves to be worshiped except Allah alone. Furthermore, the wisdom of the repetition of phrases in Surah an-Naml [27]: 60-64 is aimed at establishing true faith, avoiding acts of polytheism, and as a form of contemplation. Because by repeatedly emphasizing a subject matter, faith becomes firmly entrenched in the minds of every individual. [Artikel ini bertujuan untuk mengkaji makna pengulangan lafaz (tikrār) yang terdapat pada QS. an-Naml[27]: 60-64. Sejumlah ayat ini sekilas berbicara tentang keimanan kepada Allah sebagai ajaran yang sangat penting dan merupakan pokok dalam kehidupan manusia. Maka, menarik jika kemudian diungkap apa makna pengulangan lafaz yang diisyaratkan dalam ayat-ayat yang berbicara tentang akidah tersebut. Beberapa pertanyaan penelitian yang hendak dijawab yakni : pertama, bagaimana makna pengulangan lafaz pada QS. an-Naml[27]: 60-64?; kedua, apa hikmah yang terkandung dalam pengulangan lafaz tersebut?. Metode yang digunakan dalam penelitian ialah metode deskriptif-analitis. Berdasarkan hasil penelitian, disimpulkan bahwa makna pengulangan lafaz pada QS. an-Naml[27]: 60-64 adalah suatu “penetapan” yang terdapat pada lafaz amman di setiap permulaan ayat dan bermakna suatu “pengingkaran” pada lafaz ailāhun ma’a Allah yang berada di pertengahan ayat dan masing-masing terulang sebanyak lima kali. Pengulangan bermakna penegasan atas bukti keesaan Allah dengan sekian banyaknya ciptaan di dunia yang murni kuasa Allah tanpa campur tangan seorangpun. Sedangkan makna pengingkaran berfungsi untuk menafikan, bahwa tidak ada yang patut disembah melainkan hanya Allah semata. Selanjutnya hikmah pengulangan lafaz pada QS. an-Naml[27]: 60-64 bertujuan agar tertanam aqidah yang benar, terhindar dari perbuatan syirik, dan sebagai bentuk cara ber-tafakkur. Karena dengan diulang-ulangnya suatu materi, maka akan semakin tertanam kuatlah aqidah dalam benak setiap manusia.]